2017
DOI: 10.1007/s10698-017-9302-7
|View full text |Cite
|
Sign up to set email alerts
|

On the position of helium and neon in the Periodic Table of Elements

Abstract: Helium and neon, the two lightest noble gases, have been traditionally positioned by IUPAC in the Group 18 of the Periodic Table of Elements, together with argon, and other unreactive or moderately reactive gaseous elements (krypton, xenon, radon), and oganesson. In this account we revive the old discussion on the possible placement of helium in the Group 2, while preserving the position of neon in Group 18. We provide quantum-chemical arguments for such scenario-as well as other qualitative and quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 89 publications
2
17
0
Order By: Relevance
“…Later, aiming at further increase of reactivity, we prepared and investigated the cyanated derivative [B 12 (CN) 11 ] − , which was found to be much more electrophilic than its predecessor. It is able to bind argon at room temperature (Mayer et al, 2019) and can even form a stable adduct with extremely unreactive neon (Mayer et al, 2020) at temperatures up to 50 K. High level computational studies and investigations of the weak complexes in the cold matrix have shown that the binding energies for Ne are often even smaller than for He in similar adducts and, therefore, Ne was discussed to be the most inert NG (Frenking et al, 1990;Grandinetti, 2013;Grochala, 2018). These electrophilic anions are generated by collision induced dissociation (CID) of their gaseous precursors closododecaborate dianions [B 12 X 12 ] 2− (X=halogen, CN), which constitute a class of very stable and inert weakly coordinating anions (WCAs) (Knapp, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Later, aiming at further increase of reactivity, we prepared and investigated the cyanated derivative [B 12 (CN) 11 ] − , which was found to be much more electrophilic than its predecessor. It is able to bind argon at room temperature (Mayer et al, 2019) and can even form a stable adduct with extremely unreactive neon (Mayer et al, 2020) at temperatures up to 50 K. High level computational studies and investigations of the weak complexes in the cold matrix have shown that the binding energies for Ne are often even smaller than for He in similar adducts and, therefore, Ne was discussed to be the most inert NG (Frenking et al, 1990;Grandinetti, 2013;Grochala, 2018). These electrophilic anions are generated by collision induced dissociation (CID) of their gaseous precursors closododecaborate dianions [B 12 X 12 ] 2− (X=halogen, CN), which constitute a class of very stable and inert weakly coordinating anions (WCAs) (Knapp, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Neon‐21 nucleus (spin number I = 3/2 + , state 1 g 9/2 ) has 10 protons and 11 neutrons and thus differs by one nucleon from the magic number 20. It is the fifth most abundant element in the universe but only makes a 0.001818% contribution (by volume) to the atmosphere of Earth, and as a noble gas, its stable compounds are rare; for instance, it forms noncovalent compounds: clathrates and endohedral fullerenes . Neon possesses 14 isotopes with mass numbers from 16 up to 29.…”
Section: Introductionmentioning
confidence: 99%
“…to a reactive molecule can be substantially less favorable than binding of He. [12][13][14] In contrast to He, Ne contains occupied p-orbitals which results in higher orbital repulsion during formation of a s-bond between Ne and a reactive atom. Often, this disadvantage overcompensates the higher polarizability of Ne compared to He.…”
mentioning
confidence: 99%
“…As discussed above, this is in contrast to many theoretical investigations on other highly reactive binding sites which have shown that the dative bond to Ne is weaker than to He. [12][13][14] Thus, other interactions than the direct Ne-B bond may be of critical relevance. Electrostatic and dispersion forces play a significant role for the binding properties of the electrophilic anions of type [B 12 X 11 ] À .…”
mentioning
confidence: 99%